Association of high-density lipoprotein with P1NP and β-CTX in hospitalized patients with osteoporotic fractures: a retrospective cross-sectional study - Zhu, Cheng-bai; Zhou, Peng; Lu, Ke; Li, Chong; Wei, Yin-lin; Jin, Jian; Hu, Wen-bin; Gao, Yi-jun (Frontiers in Endocrinology, 2026)
BackgroundThe intricate relationship between bone turnover biomarkers (BTMs) and lipid profiles, particularly high-density lipoprotein (HDL), remains partially understood. This study aims to clarify how HDL is associated with BTMs, which are key indicators of bone resorption and formation, in patients hospitalized with osteoporotic fractures (OPFs). Understanding this relationship could offer new insights for osteoporosis treatment and influence future therapeutic strategies.MethodConducted at the Affiliated Kunshan Hospital of Jiangsu University from January 2017 to August 2023, this retrospective cross-sectional study involved 4782 OPFs patients requiring hospitalization or surgery; after applying the exclusion criteria, the actual valid sample size used for analysis was 712 patients. The patient’s serum HDL levels were determined, followed by the assessment of the procollagen type I N-terminal propeptide (P1NP) and the beta-C-terminal telopeptide of type I collagen (β-CTX) as outcome variables. Adjustments were made for age, gender, body mass index (BMI), and other clinical variables. The association between HDL and P1NP and β-CTX was analyzed using generalized estimating equations (GEE). Nonlinear associations were assessed via generalized additive models (GAM), with stratified analyses and threshold assessments conducted for result validation.ResultsA negative association was found between HDL levels and both β-CTX and P1NP. After adjusting for covariates, each unit increase in HDL corresponded to a decrease in P1NP by 14.37 (β = -14.37, 95% CI: -24.21 to -4.51, P < 0.01) and in β-CTX by 0.14 (β = -0.14, 95% CI: -0.22 to -0.06, P < 0.01). Threshold analysis revealed a linear relationship between P1NP and β-CTX.ConclusionThe findings reveal a negative correlation between HDL levels and both β-CTX and P1NP, suggesting a potential link between lipid metabolism and bone turnover. If validated in further studies, HDL could emerge as a predictive marker for BTMs, offering novel perspectives for osteoporosis management.